2018
DOI: 10.1111/acel.12846
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic gene transfer of BDNF promotes healthy aging in mice

Abstract: The aging process and age‐related diseases all involve perturbed energy adaption and impaired ability to cope with adversity. Brain‐derived neurotrophic factor (BDNF) in the hypothalamus plays important role in regulation of energy balance. Our previous studies show that recombinant adeno‐associated virus (AAV)‐mediated hypothalamic BDNF gene transfer alleviates obesity, diabetes, and metabolic syndromes in both diet‐induced and genetic models. Here we examined the efficacy and safety of a built‐in autoregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 47 publications
4
27
0
Order By: Relevance
“…In the CNS, EE acted to change microglial morphology and microglial gene expression in middle-aged mice. These findings appear consistent with long-term EE housing and long-term viral expression of BDNF in middle-aged mice [8,11,12]. Several of these effects remained or were compounded in response to CSF1R inhibition and depletion of microglia, suggesting that the stimulus behind hypothalamic changes causing microglial responses remains in the presence of PLX for remaining microglia.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In the CNS, EE acted to change microglial morphology and microglial gene expression in middle-aged mice. These findings appear consistent with long-term EE housing and long-term viral expression of BDNF in middle-aged mice [8,11,12]. Several of these effects remained or were compounded in response to CSF1R inhibition and depletion of microglia, suggesting that the stimulus behind hypothalamic changes causing microglial responses remains in the presence of PLX for remaining microglia.…”
Section: Discussionsupporting
confidence: 80%
“…A major candidate for this stimulus is BDNF, the central coordinator for many CNS and peripheral effects of EE. We previously demonstrated that neuronal overexpression of BDNF reproduces various effects of EE including systemic metabolism, adipose remodeling, immune modulations, cancer, and aging [9][10][11][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, hypothalamic administration of an rAAV-BDNF vector promoted healthy aging ( 83 ) largely mimicking EE effects. BDNF gene therapy was found to prevent the development of age-related metabolic decline and reduce anxiety-and depression-like behavior.…”
Section: Hsa Axis Modulation Of Healthy Systemic Agingmentioning
confidence: 99%